Inducible cardiomyocyte-specific deletion of CaM kinase II protects from pressure overload-induced heart failure - Kreußer, Michael; Lehmann, Lorenz; Wolf, Nora; Keranov, Stanislav; Jungmann, Andreas; Gröne, Hermann-Josef; Müller, Oliver J.; Katus, Hugo; Backs, Johannes (Basic research in cardiology, 2016)
CaM kinase II (CaMKII) has been suggested to drive pathological cardiac remodeling and heart failure. However, the evidence provided so far is based on inhibitory strategies using chemical compounds and peptides that also exert off-target effects and followed exclusively preventive strategies. Therefore, the aim of this study was to investigate whether specific CaMKII inhibition after the onset of cardiac stress delays or reverses maladaptive cardiac remodeling and dysfunction. Combined genetic deletion of the two redundant CaMKII genes δ and γ was induced after the onset of overt heart failure as the result of pathological pressure overload induced by transverse aortic constriction (TAC). We used two different strategies to engineer an inducible cardiomyocyte-specific CaMKIIδ/CaMKIIγ double knockout mouse model (DKO): one model bases on tamoxifen-inducible mER/Cre/mER expression under control of the cardiac-specific αMHC promoter; the other strategy bases on overexpression of Cre recombinase via cardiac-specific gene transfer through adeno-associated virus (AAV9) under control of the cardiac-specific myosin light chain promoter. Both models led to a substantial deletion of CaMKII in failing hearts. To approximate the clinical situation, CaMKII deletion was induced 3 weeks after TAC surgery. In both models of DKO, the progression of cardiac dysfunction and interstitial fibrosis could be slowed down as compared to control animals. Taken together, we show for the first time that “therapeutic” CaMKII deletion after cardiac damage is sufficient to attenuate maladaptive cardiac remodeling and to reverse signs of heart failure. These data suggest that CaMKII inhibition is a promising therapeutic approach to combat heart failure.